Waray folktales in Leyte - Tiston, Lyster C. (1989)
The desire to regain a distinct national identity and the will to contribute to the growth of Philippine folk literature were the reasons why this study on Waray folktales in Leyte was conceived.
Filipinos have always been stirred by the motivation to evolve an identity as a people and as a nation different from the rest of the world, but are passing through an identity crisis today. The cultural identity crisis we are facing is a serious problem but little attention is given to it. The crisis in folk literature or folklore identity is an even more serious dilemma, the folklore being the basic substance and essence of a people, but this has been taken for granted.
Because of the need to emerge with a distinct national identity, it is important and very helpful to study Filipino indigenous folk culture which can be reflected in the folktales of our provinces. I Leyte alone we find a rich source of uniquely diverse cultural heritage. This study, however, focuses only on barangay San Roque of Tolosa, Leyte, a village known for the existence of non-human or supernatural beings that are the subject of untold folktales.
To work on the achievement of these purposes, this study cites sample folktales which contain materials and concepts that reveal and express some aspects of the complex cultural structure of the Filipinos; evaluates the literary. specifically the metaphysical (supernatural), merits of Philippine folktales; and encourages the further exploration and study of the values of Waray folktales in particular and Philippine literature (Filipino folklore) in general.
The main purpose of this study is to gather folktales in Waray and translate these folktales into English, after which comes the interpretation, analysis and evaluation. This has been made possible through the use of the interview method. The twenty-five folktales presented here reveal some salient characteristics of the sub-culture of the inhabitants of Tolosa common to all Leyteños in one way or the other--the belief in the supernatural. The folktales tell of direct and indirect encounters with the forces of the spirit world and show how these experiences affect the local community.
The study shows some significant findings. The twenty-five folktales compiled together, whether in the original Waray version or in the English translation, share a common structure and characteristics. Since the tales told here are about the non-human spirits (enkantos), the common theme is healing and harmony with nature, with the environment and with the spirits. The subjects are the human beings who are victims or friends of the enkantos. These indigenous folktales are characteristically short and simple in form, and suggest notions of conduct.
In the final analysis, it can be concluded that Waray folkatales are influenced by the Filipino people's deeply entrenched belief in the supernatural world; the citizens of which are God, the non-human spirits, and the souls of the departed, though oftentimes it is doubted whether or not these three can actually co-exist together in one world. This belief can be attributed to the animistic nature of Philippine culture. Waray folktales are a valid representation of the folk culture of the Filipinos.
Undergraduate thesis (B.A. Communication Arts)--University of the Philippines, College Tacloban.
Keywords: Waray folktales -- Leyte